Strategic Workforce Management Navigating Retention, Succesion and Knowledge - Fadillah Ismail (2025)
This book provides an insightful guide into strategic workforce management, focusing on retention, succession planning, and knowledge management. It addresses the evolving challenges organizations face, such as demographic shifts and global crises, highlighting the importance of human capital in achieving business objectives. Through a mix of theory and case studies, the book offers strategies for maintaining a skilled workforce, ensuring leadership continuity and managing knowledge for competitive advantage. It emphasizes the critical role of strategic planning in fostering an environment that encourages employee retention, smooth leadership transitions, and innovation, making it a valuable resource for navigating the complexities of modern human resource management.